IDENTIFIKASI JENIS-JENIS ALAT TANGKAP IKAN RAMAH LINGKUNGAN DI KAWASAN KONSERVASI KEPULAUAN PADAIDO KABUPATEN BIAK NUMFOR - Susi Sartika; Fanny F.C. Simatauw; Fitriyah Irnawati E. Saleh; Sampari S Suruan; Fredy C. Eldiester Dan; Setiawan Mangando; Yulianti Elisabet Demena; Jamaludin; Frits N. Y Rumbino (Yayasan Nusantara Hasana Berdikari, 2023)
Identifying types of environmentally friendly fishing gear and analyzing the level of environmental friendliness of fishing gear in the Padaido Islands Conservation Area which is to produce environmentally friendly fishing gear based on FAO 1945 criteria. The purpose of this field work practice is to analyze the level of environmental friendliness of each fishing gear and the catch of the fishing gear. This field work practice was carried out for 1 month, namely July 3 - August 11, 2023. Data collection techniques in this field work practice are carried out by conducting field observations which by conducting interviews directly with respondents (Fishermen). This field work practice uses primary data which is data collected or obtained directly from fishermen in the Diido Islands conservation area by interviewing fishermen using questionnaires. Data analysis used in this fieldwork practice is descriptive analysis, according to Nawawi (1998) descriptive analysis is a problem-solving procedure investigated by describing / describing the current state of the subject / object of research based on facts that appear or as they are and are also assisted by using Microsoft Excel 2010. Line fishing is one of the most environmentally friendly fishing gears in the Padaido Islands with an environmental friendliness score of 33.58 and is also one of the most widely used fishing gears in the Padaido Islands, tonda fishing gear has a score of 31.12, gill net fishing gear is 29 and molo rifle fishing gear is 23.2, Fish caught based on fishing gear are line fishing with 10 speises, tonda fishing gear 6 species, gill net 8 species and molo rifle 3 species.